Constraints on the presence of platinum and gold in the spectra of the kilonova AT2017gfo. Issue 3 (2nd July 2021) - Gillanders, J H; McCann, M; Sim, S A; Smartt, S J; Ballance, C P
ABSTRACT: Binary neutron star mergers are thought to be one of the dominant sites of production for rapid neutron capture elements, including platinum and gold. Since the discovery of the binary neutron star merger GW170817, and its associated kilonova AT2017gfo, numerous works have attempted to determine the composition of its outflowing material, but they have been hampered by the lack of complete atomic data. Here, we demonstrate how inclusion of new atomic data in synthetic spectra calculations can provide insights and constraints on the production of the heaviest elements. We employ theoretical atomic data (obtained using $\small {\rm GRASP}^{0}$ ) for neutral, singly and doubly ionized platinum and gold, to generate photospheric and simple nebular phase model spectra for kilonova-like ejecta properties. We make predictions for the locations of strong transitions, which could feasibly appear in the spectra of kilonovae that are rich in these species. We identify low-lying electric quadrupole and magnetic dipole transitions that may give rise to forbidden lines when the ejecta becomes optically thin. The strongest lines lie beyond 8000 Å, motivating high quality near-infrared spectroscopic follow-up of kilonova candidates. We compare our model spectra to the observed spectra of AT2017gfo, and conclude that no platinum or gold signatures are prominent in the ejecta. From our nebular phase modelling, we place tentative upper limits on the platinum and gold mass of ≲ a few 10 −3  M⊙, and ≲ 10 −2  M⊙, respectively. This work demonstrates how new atomic data of heavy elements can be included in radiative transfer calculations, and motivates future searches for elemental signatures.